Inflammatory Cells Accelerated Carotid Artery Calcification via MMP9: Evidences From Single-Cell Analysis - Liang, Xiaobing; He, Wanbing; Zhang, Hua; Luo, Dongling; Zhang, Zhengzhipeng; Liu, Aiting; Wang, Jinkai; Huang, Hui (Frontiers in Cardiovascular Medicine, 2021)
Background: Vascular calcification (VC) is an important predictor of prognosis in atherosclerosis, the phenotypic transformation of vascular smooth muscle cells (VSMCs) is thought to be a process of VC. However, the implications and potential mechanisms for VSMCs phenotypic transition remain unknown. Methods: To study the transformation of vascular smooth muscle cells (VSMCs) in the calcification early period, we analyzed single-cell sequencing data from carotid artery calcified core and paracellular tissue, based on the results of enrichment analysis and protein-protein interaction analysis. Upstream transcription factors were tracked and finally the results were validated using the MESA database. Results: We successfully identified a subpopulation of inflammatory macrophage-like VSMCs and determined that MMP9 is an important factor in the phenotypic transformation of VSMCs. We found that RELA regulates MMP9 expression and that knockdown of RELA attenuated MMP9 expression and reduced the expression of BMP2 and the macrophage marker LGALS3 in vascular smooth muscle in inflammatory states, while serum levels of MMP9 correlated significantly with the inflammatory response. Conclusion: This study reveals that the phenotypic transformation of VSMCs can be regulated by modulating MMP9, providing a new idea for the early treatment of VC.